Here's the question you clicked on:
cbrusoe
The figure below shows two triangles EFG and KLM. Which step can be used to prove that triangle EFG is also a right triangle? Answer Prove that a + b is greater than c in triangle EFG so c2 = a2 + b2. Prove that KL = EF so in triangle KLM c2 = a2 + b2 which makes triangle EFG a right triangle. Prove that the sum of the squares of a and c in triangle EFG is greater than square of b in triangle KLM. Prove that the sum of the squares of a and b in triangle KLM is greater than square of c in triangle EFG.
i think it may be the first option but not sure
to prove that EFG is right you have to prove that c^2 = a^2 + b^2 but since KLM is right => KL= a^2 +b^2 thus c must be equal to KL the second choice (Prove that KL = EF so in triangle KLM c2 = a2 + b2 which makes triangle EFG a right triangle)
ok that makes sense, thank-you =)